Effectiveness of Schema Therapy and Acceptance and Commitment Therapy (ACT) on the Mental Health of Conflicted Couples - Zarei, Alireza; Bakshipour, Abolfazl; Mohammadipour, Mohammad (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to investigate the effectiveness of schema therapy and Acceptance and Commitment Therapy (ACT) on the mental health of conflicted couples. Methods and Materials: This study is a quasi-experimental research with a pre-test, post-test, and follow-up design, including a control group. The study population consisted of couples who visited counseling centers and the Social Emergency Unit of the Welfare Organization in Bojnord in 2022, selected through a convenience sampling method. The schema therapy experimental group received seven 120-minute sessions, and the ACT experimental group participated in eight 120-minute sessions. The control group did not receive any training. The research instrument was the General Health Questionnaire (GHQ) by Goldberg and Taghavi (2001). Data were analyzed using SPSS 25 software with multivariate repeated measures analysis of variance and Bonferroni post hoc tests. Findings: The findings indicated the effectiveness of schema therapy and ACT in improving the mental health of conflicted couples, with sustained effects reported at the follow-up stage. Additionally, ACT demonstrated greater effectiveness. Conclusion: Based on the findings of this study, schema therapy and Acceptance and Commitment Therapy can be utilized to enhance the mental health of conflicted couples.